1997
DOI: 10.1111/j.2044-8325.1997.tb00656.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hours of work on health: A meta‐analytic review

Abstract: A quantitative and qualitative review of existing literature on working hours and health was carried out. Meta‐analyses were performed on 21 study samples. Results indicated small, but significant positive mean correlations between overall health symptoms, physiological and psychological health symptoms, and hours of work. Qualitative analysis of 12 other studies supported these findings of a positive relationship between hours of work and ill‐health. Different factors which may obscure the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
420
2
9

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 598 publications
(448 citation statements)
references
References 1 publication
17
420
2
9
Order By: Relevance
“…Of these, six studies met the inclusion criteria and a further four were identified from referred publication searches, hand search, and from the reference lists of published reviews. We excluded metaanalyses (but extracted relevant studies from those) (18,19,25,26), reviews (5, 8-17, 21, 23), and books (20,22,24). We also excluded studies with overlapping data with selected studies (33)(34)(35)(36)(37)(38)(39)(40), those without adjustment for baseline mental health (41)(42)(43), and those prospective studies in which exposure and outcome were temporally overlapping (44,45).…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, six studies met the inclusion criteria and a further four were identified from referred publication searches, hand search, and from the reference lists of published reviews. We excluded metaanalyses (but extracted relevant studies from those) (18,19,25,26), reviews (5, 8-17, 21, 23), and books (20,22,24). We also excluded studies with overlapping data with selected studies (33)(34)(35)(36)(37)(38)(39)(40), those without adjustment for baseline mental health (41)(42)(43), and those prospective studies in which exposure and outcome were temporally overlapping (44,45).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Of the three previous meta-analyses of the association between long working hours and mental health, two were published in 1997 (18) and 2008 (19), and were mainly based on cross-sectional data. They reported a weak linear correlation between hours worked and "mental strain", which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately one-fifth of U.S. employees work more than 48 hours a week (International Labour Organization, 2007). According to many reviews of the literature (see, for example, Sparks et al, 1997), the stress and fatigue that sometimes result from longer work hours can affect employee health and well-being. In addition, longer hours may affect work-family conflict, leading to further stress in both personal and professional settings (Major, Klein, and Ehrhart, 2002).…”
Section: Work and Organizational Characteristicsmentioning
confidence: 99%